Diagnostic tenoscopy of the carpal sheath with a needle arthroscope in standing sedated horses. (25th January 2020) - Miagkoff, Ludovic; Bonilla, Alvaro G.
Abstract: Objective: To investigate the use of a needle arthroscope for diagnostic tenoscopy of the carpal sheath in standing horses. Study design: Experimental study. Sample population: Six forelimbs for the cadaveric part of the study and six horses for the in vivo part of the study. Methods: Six cadaveric limbs were used to perform carpal sheath tenoscopy with a 1.2‐mm‐diameter needle arthroscope (65 and 100 mm long), followed by tenoscopy with a 4‐mm arthroscope through a standard proximolateral approach. Then, unilateral standing carpal sheath tenoscopy was performed in six healthy sedated horses with a 65‐mm‐long needle arthroscope. Limbs were maintained in flexion during the procedure by using a custom‐made splint and base. Degree of tenoscopic evaluation, safety, horse tolerance, and complications were recorded. Results: Visibility at the most distal aspect of the sheath was absent for the needle arthroscopes vs a standard arthroscope. The maneuverability with a 65‐mm needle arthroscope was excellent and allowed exhaustive visualization of the proximal region of the carpal sheath in cadaveric limbs and standing horses (six of six). However, visualization of the intertendinous recess was partial in most horses (four of six) vs cadavers (complete in six of six) because of remaining flexor tendon tension in standing horses. No major complications were encountered. Conclusion: Standing carpal sheath tenoscopy allowed a safe and thorough evaluation of most structures in the proximal region of the sheath and offers an alternative diagnostic technique. Clinical significance: Horses with unrewarding results after traditional imaging or that require an accurate diagnosis before treatment may benefit from this alternative procedure.